382 Timing of paediatric presentation to the emergency department during the COVID-19 lockdown. Issue 12 (23rd November 2020) - Harwood, Rachel; Roland, Damian; Patel, David; Mendes, Fiona; Fitzsimmons, Andrew; Mullen, Niall; James, David; Bayreuther, Jane; Peckham, Clare
Abstract : Aims/Objectives/Background: Paediatric presentations to the emergency department (ED) reduced significantly during the COVID-19 lockdown. Concerns were raised that children were coming to harm as a result of delayed presentations to ED and rapid guidance was produced for parents to highlight red and amber symptoms which should prompt ED review. NHS 111 responses were also adapted for children to facilitate rapid recognition of the sick child. The aim of this rapid surveillance project was to objectively describe the proportion of children who had a delayed presentation to ED during the COVID-19 lockdown and their need for admission. Methods/Design: Prospective anonymous data collection on children presenting to ED during periods between 20th April and 8th July 2020 in 7 trusts in England and Northern Ireland. Clinicians (doctors and advance care practitioners) were asked to feedback at the time of patient dispostion about whether the parents had reported a delay in presenting to hospital the parents had experienced a delay secondary to another service provider (primary care/111) there was no delay in presentation they were uncertain as to whether there was a delay. Data was a collected via an approved website with appropriate data goverance. Results/Conclusions: 1637 patients patient entries were recorded, the majority in May 2020 (86%). Patient characteristics and outcomes are shown in table 1 . Diagnosis of 11 patients with delayed presentation requiring admission: sepsis, abdominal pain of unclear cause, abscess, bronchiolitis, headache, GORD, DKA, testicular torsion and viral induced wheeze. 1 in 24 children were reported to have delayed presentation during lockdown and a small number of these children required PICU admission. Overall the data are reassuring that the majority of children are brought to ED appropriately. Ongoing messaging for parents regarding red and amber symptoms continues to be important, particularly in the event of any further lockdowns.